2019
DOI: 10.1097/01.ogx.0000557738.46753.6a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the T-Cell Response to Polypropylene Mesh in Women With Complications

Abstract: (Abstracted from Am J Obstet Gynecol 2019;220:187.e1–187.e8) Polypropylene mesh has been widely used as surgical treatment for pelvic organ prolapse and stress urinary incontinence. Although mesh provides favorable functional and anatomic outcomes, its use has been limited by complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The abundant expression of CD68, CD45, as well as CD8 within the FBG, suggested the possibility that macrophages alone may not be playing the decisive part. Consistently, Tennyson et al (2018) analyzed tissue reactions to explanted pelvic floor meshes and confirmed the presence of abundant lymphocytes, for example, CD4+ helper T cells, CD8+ cytotoxic T cells, or FOXP3+ regulatory T cells. Furthermore, our observation of widespread positive staining of different markers suggested that cells may co‐express some of them.…”
Section: Introductionmentioning
confidence: 65%
“…The abundant expression of CD68, CD45, as well as CD8 within the FBG, suggested the possibility that macrophages alone may not be playing the decisive part. Consistently, Tennyson et al (2018) analyzed tissue reactions to explanted pelvic floor meshes and confirmed the presence of abundant lymphocytes, for example, CD4+ helper T cells, CD8+ cytotoxic T cells, or FOXP3+ regulatory T cells. Furthermore, our observation of widespread positive staining of different markers suggested that cells may co‐express some of them.…”
Section: Introductionmentioning
confidence: 65%
“…Moreover, underlying pro-inflammatory conditions, such as obesity, diabetes, smoking, and ageing contribute to complications in other biomaterial applications, such as breast or orthopaedic implants 61,62 , but have not been investigated specifically in POP or SUI mesh complications. 59,63 [H1] Surgical risk factors Surgical risk factors, such as the experience of the surgeon and surgical technique, have been linked to rates of mesh complications following pelvic floor reconstructive surgery. 18,53 Some clinical studies demonstrate that avoiding a vaginal incision suture line being in direct contact with the mesh material could decrease mesh exposure.…”
Section: [H1] Patient-specific Risk Factorsmentioning
confidence: 99%
“…However, some studies have examined explanted PPL mesh and vaginal tissue from patients treated for POP or SUI who had mesh removal because of pain or exposure. 29,46,63,[81][82][83][84] These studies often combine patients with SUI and POP, so understanding how responses differ between biological niches is not always possible. Typical of the FBR, a fibrous capsule and a dense cellular infiltrate of predominantly macrophages has been observed around the excised tissues (Figure 1).…”
Section: [H1] Patient-specific Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism of such post-surgical complications is poorly understood, recent studies in non-human primates have shown that such complications stem from undesirable and prolonged immune responses and may also be associated with decreased vaginal collagen, elastin, and smooth muscles [ 9 , 40 ]. Explanted meshes from women also suggested that sub-optimal meshes that lead to erosion and pain pique both the innate and adaptive immune systems of the body [ 19 , 118 ]. Furthermore, it is now becoming clear that even lightweight microporous stiff meshes are associated with exposures and erosions, with increased matrix metalloproteinase (MMP) activity, which leads to degradation of muscularis layer/smooth muscle content and an increase in the ratio of collagen subtypes III/I [ 42 , 45 ].…”
Section: Practical Considerations In the Design Of New-generation mentioning
confidence: 99%